Effect of exercise on TRB3 and GLUT4 expression following glucose loading in chronic leptin treated rat / Siti Nurr Atika Mohd Sanif - Mohd Sanif, Siti Nurr Atika (2016)
Leptin affects insulin secretion and action through either a central or peripheral mechanism. It increases glucose metabolism and energy expenditure. Though overweight and obese individuals have been reported to have high circulating leptin level, these effects of leptin are not evident. Exercise, on the other hand, has been found to increase glucose uptake in these individuals. This study examined the effect of chronic leptin treatment and exercise on glucose homeostasis in Sprague-Dawley rats. Eight-week old rats were treated with either intraperitoneal injection of normal saline (Control; n=8), or leptin (60 |μg/kg body weight/day; Leptin; n=8), or leptin and exercise (60 | μg /kg body weight/day plus running on a treadmill every other day for 30 minutes at a speed of 30 m/min with 10° inclination; Leptin-exercise; n=8) or exercise only (running every other day for 30 minutes at a speed of 30 m/min with 10° inclination on a treadmill; Exercise; n=8) for six weeks. Following six weeks of treatment, glucose challenge was performed by intravenous infusion of 100 mg/ml of glucose for 5 minutes. Skeletal muscle tissues were collected at 0, 15, and 30 minutes respectively during the protocol for blood glucose, serum glucose, insulin, TRB3, GLUT4 protein and mRNA expression determination. Liver was harvested for TRB3 and GLUT2 protein and mRNA determination. Data were analyzed using One Way ANOVA with post-hoc analysis, and expressed as mean ± standard error of mean (SEM). Glucose clearance was delayed in the leptin group. This delay in glucose clearance might be associated with the significantly lower GLUT2 mRNA expression in the liver of leptin-treated rats. Leptin treatment also significantly reduced TRB3 mRNA levels in both muscle and liver tissues. More importantly, exercise reversed the leptin effects by promoting glucose clearance despite a significantly lower insulin peak, indicating a significant increase in insulin sensitivity. Exercise also significantly reduced TRB3 mRNA expression levels and increased GLUT4 mRNA levels in the muscle. In conclusion, six weeks of daily leptin administration resulted in delayed glucose clearance but concurrent exercise however prevented these effects of leptin by promoting glucose clearance and increasing insulin sensitivity.